2009
DOI: 10.1007/s10517-010-0793-7
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Guidelines for Genetic Safety Testing of Cell Transplants

Abstract: A combination of karyotyping and aneuploidy analysis by interphase fluorescent in situ hybridization is a sensitive method for evaluation of genetic stability of stem cell cultures. The methodology and specific features of preparing and analyzing the cytogenetic preparations are described as exemplified by human multipotent mesenchymal stromal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Hybridization mixture for two-color FISH contained samples for three chromosome pairs: X and Y, 1 and 8, 6 and 11. Analysis was carried out as described previously [3], a total of 500 interphase nuclei were analyzed for each chromosome pair three times. Cells with one or three signals by one chromosome and two signals by the other (for pairs 1 and 8, 6 and 11), without signals or with two signals by one chromosome and one signal by the other chromosome (for X and Y pair) were referred to aneuploid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization mixture for two-color FISH contained samples for three chromosome pairs: X and Y, 1 and 8, 6 and 11. Analysis was carried out as described previously [3], a total of 500 interphase nuclei were analyzed for each chromosome pair three times. Cells with one or three signals by one chromosome and two signals by the other (for pairs 1 and 8, 6 and 11), without signals or with two signals by one chromosome and one signal by the other chromosome (for X and Y pair) were referred to aneuploid.…”
Section: Methodsmentioning
confidence: 99%
“…The use of nanoparticles (NP) is a promising technology for the manufacturing cosmetic articles, drugs, biomimetics, lubricants, and fuel additives, protective and fortifying fi lms, composite, textile, packing materials, lacquers and paints [3]. The creation of nanoindustry is a priority trend of economy in Russia; carbon NP is one of the priorities in the development of materials [1,6].…”
mentioning
confidence: 99%
“…ND, not detected; ns, not significant stable during culturing in vitro [42][43][44][45][46][47][48]. On the contrary, abundant recent studies have revealed that human MSCs exhibited spontaneous genomic alternation with increased passage number [49][50][51][52][53][54]. Previous chromosomal profiling studies also provide that karyotypical abnormalities and chromosomal instability in early passaged human MSCs disappear during the extended passage [51,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In majority of clinical trials involving MSCs published to date, the cells are used at early passages (no more than passage 5). However, cells with clonal aneuploidy and translocations have been described already at 1 st and 4 th passages of various MSC lines [ 3 , 4 , 5 ]. An extensive body of data suggests that MSCs are relatively genetically stable during culturing in vitro [ 6 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%